Professional real estate development - Peiser, Richard B (Urban Land Institute, 2012)
Includes bibliographical references and index; Acknowledgments -- Foreword -- Introduction -- Organizing for development -- Land development -- Multifamily residential development -- Office development -- Industrial development -- Retail development -- Trends and issues -- Index